Cranial Vault Distraction in Nonsyndromic Sagittal Synostosis. Issue 1 (14th September 2021) - Quinlan, Christine S.; Theopold, Christoph; Laffan, Eoghan; Caird, John; Murray, Dylan
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: A multitude of operations exists for the treatment of patients with sagittal craniosynostosis presenting after 6 months of age, of which total cranial vault remodeling now provides the most reliable aesthetic outcome. As our national craniofacial center evolved and began to develop a comprehensive multi-disciplinary team to manage complex surgical cases, we offered cranial vault distraction as an alternative to more invasive surgery for late presentation nonsyndromic scaphocephaly. The authors conducted a retrospective review of all patients undergoing this procedure. An average distraction distance of 39.4 mm was achieved in 15 patients aged 1 to 9 years. As a result, the cephalic index changed an average of 4%. The mean transfusion volume in the perioperative period was 32.47% of estimated blood volume. There were 2 complications requiring further operative intervention and distraction was stopped early in 1 patient. The authors propose that internal calvarial distraction is a viable alternative to total cranial vault remodeling for the management of late presentations of sagittal craniosynostosis.